2017
DOI: 10.1093/jme/tjw222
|View full text |Cite
|
Sign up to set email alerts
|

Repellent and Larvicidal Activity of the Essential Oil From Eucalyptus nitens Against Aedes aegypti and Aedes albopictus (Diptera: Culicidae)

Abstract: Dengue, chikungunya, and yellow fever are important vector-borne diseases transmitted by female mosquitoes when they feed on humans. The use of repellents based on natural products is an alternative for personal protection against these diseases. Application of chemicals with larvicidal activity is another strategy for controlling the mosquito population. The repellent and larvicidal activities of the essential oil from Eucalyptus nitens were tested against Aedes aegypti and Aedes albopictus, the main vectors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 62 publications
3
11
0
Order By: Relevance
“…In previous studies, a similar trend was observed when the essential oils of Eucalyptus, Camaldulensis, Eucalyptus nitens, and Cinnamomum osmophloeum were evaluated against Ae. albopictus, respectively [55][56][57]. Although our results of different levels of mortality achieved by different plant derivatives are in accordance with other reports, further studies are required to find out the mode of action of the extract and the constituents of S. alopecuroides toward the overall toxicity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In previous studies, a similar trend was observed when the essential oils of Eucalyptus, Camaldulensis, Eucalyptus nitens, and Cinnamomum osmophloeum were evaluated against Ae. albopictus, respectively [55][56][57]. Although our results of different levels of mortality achieved by different plant derivatives are in accordance with other reports, further studies are required to find out the mode of action of the extract and the constituents of S. alopecuroides toward the overall toxicity.…”
Section: Discussionsupporting
confidence: 89%
“…The repellent activity provided by S. alopecuroides extract was also better than previously used repellents against Ae. albopictus, such as the E. nitens essential oil, and its main component, 1,8-cineole [57].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the other constituents of the essential oil have antagonistic interactions with eucalyptol. The low larvicidal activity of eucalyptol (1,8-cineol) has been reported previously against larvae of Aedes aegypti [ 33 ], Anopheles anthropophagus [ 34 ] and Culex pipiens [ 35 ], however it has been shown to be effective as a repellent in foods and highly effective as an ovipositional repellent [ 33 ], however the effect did not last for more than 30 min [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…had the highest larvicidal activity while Eucalyptus saligna Sm. displayed higher repellency than Eucalyptus nitens (H. Deane & Maiden) Maiden [61][62][63].…”
Section: Essential Oilsmentioning
confidence: 96%
“…The main constituents were carvone (11) (48.6%), cis-carveol (12, 21.3%) and limonene (13, 11.3%) [72]. Another spice with larvicidal acitivity was turmeric [Curcuma longa L. (Zingiberaceae)] whose rhizome essential oil demonstrated LC 50 65.51 µg/mL [62]. Similarly, Porophyllum ruderale (Jacq.)…”
Section: Essential Oilsmentioning
confidence: 99%